Probability timed automata for investigating communication processes - Piech, Henryk; Grodzki, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
Exploitation characteristics behaves as a decreasing valors factor (DVF) which can be connected with degradation processes. It is a structure that consists of independent attributes which represent situations generally connected with a given exploitation factor. The multi-attribute structure contains attributes directly and indirectly referring to the main factor.
Keywords: protocol logic; probabilistic timed automata; communication security